WORK-LIFE BALANCE AMONG SMALL CONSTRUCTION FIRM OWNERS A PHENOMENOLOGICAL STUDY OF CV. MALALA IN INDONESIA - Della Aprillia Sari; Iing Sri Hardiningrum (SOSIOEDUKASI, 2025)
The research seeks to examine the experience of the proprietor of CV.MALALA in achieving work-life balance amidst the demands of theconstruction industry. A qualitative phenomenological approach was employed to gather data via in-depth interviews and non-participatory observations. Research findings indicate that employment pressures stem from two primary factors: technical (complete readiness for projects, including during holidays) and administrative (bureaucratic intricacies in project compilation). Effective family communication and support can mitigate conflicts between professional and familial roles, which frequently arise. The employed coping mechanisms encompass spiritual practices (sholawatan, mosque involvement, detachment) and social support (reciprocal assistance among colleagues, familial support). Participants characterize work-life balance as a blend of professional and personal life that mutually reinforces each aspect, rather than as a separation. These findings reinforce role theory, conservation of resources theory, social support theory,and work-family enrichment theory, highlighting the significance of emotional, spiritual, and social equilibrium amidst work-related stress in the construction sector.